The coach-athlete relationship and hope of university athletes of individual modalities from Paraná (Research, Society and Development, 2020)
They are increasing in the sporting context the investigations on the virtues of the human being, from the positive psychological. Moreover, besides these intrapersonal factors, the social interactions established in training and competitions have been essential for the personal growth and performance of athletes and coaches. This study aimed to investigate the coach-athlete relationship and the hope of athletes. Participated in this study 101 university athletes of different individual modalities, of both gender (20,48±2,54 years), participants of the 56th Paraná University Games (JUPs). Were used the Dispositional Hope Scale (DHS) and the Coach-Athlete Relationship Questionnaire (CARTQ) - athlete version. Data were analyzed using the Shapiro Wilk, Mann Whitney, Kruskall-Wallis and Spearman correlation coefficients (p